Engineered red blood cell membrane for sensitive and precise electrochemical detection of salivary exosomes. Issue 48 (7th December 2021) - He, Libang; Shao, Meiying; Xu, Jue; Chen, Hao
Abstract : An electrochemical method is developed for salivary exosome detection using red blood cell membranes engineered with CD63 aptamer. Abstract : As a kind of promising non-invasive biomarker, exosomes naturally occurring in saliva have recently attracted considerable attention in view of their potential use in the diagnosis of oral diseases. Herein, we propose a new electrochemical method for the sensitive and precise detection of salivary exosomes. A red blood cell membrane (RBCM) engineered with CD63 aptamer is the core element of the method and is used to camouflage a gold electrode, thus giving the electrode superior antifouling and targeting ability. Target exosomes presented in saliva are recognized and captured by the highly specific interaction between the exosomal CD63 and the aptamers engineered in RBCM. Then, silver nanoparticles modified with CD63 aptamers are recruited onto the electrode surface to generate significant electrochemical signals, which enables the sensitive detection of target exosomes. By using human oral squamous cell carcinoma CAL27 cell-derived exosomes as a model, the method allows target salivary exosome detection in a wide linear range from 5 × 10 2 to 1 × 10 6 particles per mL and a low detection limit of 2.07 × 10 2 particles per mL. Moreover, the method displays good reproducibility and is feasible for detecting target exosomes with high precision in saliva samples. Overall, the method may provide a useful tool for salivary exosome detection and may have great potential for practical use in the clinical diagnosis of oral diseases.